RATIONAL EMOTIVE THERAPY DALAM MENANGANI NEGATIVE THINKING PERSPEKTIF POSITIVISME LOGIS - Ainun Sakinah (Transformatif, 2019)
This article is discussed Rational Emotional Therapy in negative thoughts with perspective of logical positivism studies. The basic idea of this research is to prove and challenge the irrational counselee, which irrational thinking will be replaced by more rational and logical thoughts in accordance with Rational Emotional Therapy and applied the verification method that proposed by the Vienna Circle. The application of verification methods is done by making observations and direct interviews with the closest person with negative thoughts, irrational thoughts, and counselee changes. Verifying and proving the agreement cannot give a subjective or opinion based on its own but intended for the objective.